Exploring the composition and structure of milk and meat value chains, food safety risks and governance in the Addis Ababa and Oromia regions of Ethiopia - Nyokabi, Ndungu S.; Lindahl, Johanna F.; Phelan, Lisette T.; Berg, Stefan; Gemechu, Gizachew; Mihret, Adane; Wood, James L. N.; Moore, Henrietta L. (Frontiers in Sustainable Food Systems, 2023)
Demand for animal-source foods (ASF) is increasing globally, driven by a growing human population and changing dietary preferences. ASF, such as milk and meat, are nutritious foods that are rich in essential nutrients; they constitute an important part of diets globally, particularly, in the Global South. There is an imperative to improve food safety governance to ensure access to safe, high-quality ASF. Currently, low compliance with good agricultural practices (GAPs) and food safety standards is a major public health concern due to the high prevalence of foodborne diseases in global south countries. This study examines the composition and structure of milk and meat value chains and explores the food safety governance in the Addis Ababa and Oromia regions of Ethiopia. Stakeholder discussions and key informant interviews and participant observation were undertaken to collect data on milk and meat value chain actors’ perceptions of opportunities and constraints to improving access to safe, high-quality milk and meat products. The results reveal that there was low compliance with rules and standards by milk and meat value chain actors which could compromise food safety and quality and expose consumers to public health risks. There was stricter enforcement of GAPs and food safety standards in the case of milk and meat products destined for export compared to products sold in the local markets. The main challenges to compliance with food safety regulations were actors’ low knowledge, small profit margins, absence of critical food safety infrastructure such as electricity and road and low access to capital to invest in the recommended equipment such as aluminium containers, coolers and fridges. This paper concludes there is a need for improved communication and tailored training for value chain actors to improve their knowledge of food safety risks. Furthermore, there is a need for food safety standards and interventions that are designed to fit the local social, cultural and economic context as this will increase actors’ incentive to comply with rules governing food safety and quality.